Interferon Gamma ELISPOT Testing as a Risk‐Stratifying Biomarker for Kidney Transplant Injury: Results From the CTOT‐01 Multicenter Study. Issue 12 (30th July 2015) - Hricik, D. E.; Augustine, J.; Nickerson, P.; Formica, R. N.; Poggio, E. D.; Rush, D.; Newell, K. A.; Goebel, J.; Gibson, I. W.; Fairchild, R. L.; Spain, K.; Iklé, D.; et al.
Abstract : Previous studies suggest that quantifying donor‐reactive memory T cells prior to kidney transplantation by interferon gamma enzyme‐linked immunosorbent spot assay (IFNγELISPOT) can assist in assessing risk of posttransplant allograft injury. Herein, we report an analysis of IFNγELISPOT results from the multicenter, Clinical Trials in Organ Transplantation‐01 observational study of primary kidney transplant recipients treated with heterogeneous immunosuppression. Within the subset of 176 subjects with available IFNγELISPOT results, pretransplant IFNγELISPOT positivity surprisingly did not correlate with either the incidence of acute rejection (AR) or estimated glomerular filtration rate (eGFR) at 6‐ or 12‐month. These unanticipated results prompted us to examine potential effect modifiers, including the use of T cell‐depleting, rabbit anti‐thymocyte globulin (ATG). Within the no‐ATG subset, IFNγELISPOT neg subjects had higher 6‐ and 12‐month eGFRs than IFNγELISPOT pos subjects, independent of biopsy‐proven AR, peak PRA, human leukocyte antigen mismatches, African‐American race, donor source, and recipient age or gender. In contrast, IFNγELISPOT status did not correlate with posttransplant eGFR in subjects given ATG. Our data confirm an association between pretransplant IFNγELISPOT positivity and lower posttransplant eGFR, but only in patients who do not receive ATG induction. Controlled studies are needed to test the hypothesis that ATG induction is preferentially beneficial to transplant candidates with high frequencies of donor‐reactive memory T cells. Abstract : Analysis of data from the Clinical Trials in Organ Transplantation‐01 study associates a positive pretransplant donor‐reactive ELISPOT assay for interferon gamma with low posttransplant glomerular filtration rate, but only in patients who do not receive T cell‐depleting induction therapy with rabbit anti‐thymocyte globulin.